Teachers today: skills and initial training as priority axes in their identity construction - Callealta Oña, Leopoldo; Donoso González, Macarena; Camuñas, Nuria (Journal of Learning Styles, 2020)
Currently there is consensus on the idea that the quality of education systems depends largely on their teachers. They are expected to become enthusiastic, curious and in continuous training professionals (OECD, 2018). In response to this demand, the debate about the competence profile and the initial training of the aspiring teachers has been reopened, variables that have been shown to be closely related to the formation of the teaching professional identity. In this work, as a result of a broader investigation aimed at analyzing the variables involved in the construction of the teaching identity of the secondary school teacher, a critical review is presented with the aim of analyzing to what extent the development of competencies and Initial teacher training in establishing your own identity. It is concluded that the initial training in aspiring secondary school teachers is the key piece for the professional development of the teacher. This will be formed from the construction of the professional identity and the consolidation of the professional competences necessary to develop their educational work.